Poor clinical response in rheumatoid arthritis is the main risk factor for diabetes development in the short-term: A 1-year, single-centre, longitudinal study. - Piero Ruscitti; Francesco Ursini; Paola Cipriani; Vasiliki Liakouli; Francesco Carubbi; Onorina Berardicurti; Giovambattista De Sarro; Roberto Giacomelli (PLoS ONE)
Objectives Despite of the European League Against Rheumatism (EULAR) provided different sets of recommendations for the management of cardiovascular risk in inflammatory arthritis patients, it must be pointed out that cardiometabolic comorbidity, such as type 2 diabetes (T2D), remains still underdiagnosed and undertreated in patients affected by rheumatoid arthritis (RA). Methods In this work, we designed a single centre, prospective study in order to better investigate the occurrence of T2D during the course of 1 year of follow-up. Furthermore, we evaluated the role of both traditional cardiovascular and RA-specific related risk factors to predict the occurrence of new T2D. Results In this study, we evaluated 439 consecutive RA patients and we observed that 7.1% of our patients (31/439) developed T2D, after 12 month of prospective follow-up. The regression analysis showed that the presence of high blood pressure, the impaired fasting glucose (IFG) at the first observation and the poor EULAR-DAS28 response, after 12 months of follow-up, were significantly associated with an increased likelihood of being classified as T2D. Similarly, we observed that 7.7% of our patients (34/439) showed IFG after 12 months of prospective follow-up. The regression analysis showed that the presence of high blood pressure and the poor EULAR-DAS28 response after 12 months of follow-up, were significantly associated with an increased likelihood of showing IFG. Conclusions Our study supports the hypothesis of a significant short-term risk of T2D in RA patients and of a close associations between uncontrolled disease activity and glucose metabolism derangement. Further multicentre, randomised-controlled studies are surely needed in order to elucidate these findings and to better ascertain the possible contribution of different therapeutic regimens to reduce this risk.